A Positive Legacy of Trauma? The Role of Perceived Social Support on Mental Health Among Earthquake Survivors During the COVID-19 Outbreak - Wang, Dongfang; Zhai, Shuyi; Chen, Jiaqiao; Chen, Yao; Hua, Shiming; Wang, Chengchen; Fan, Fang; Liu, Xianchen (Frontiers in Psychiatry, 2022)
Background: People with prior experience of severe trauma may be particularly vulnerable in the face of COVID-19 pandemic. However, little is known about mental health problems among prior trauma survivors during the pandemic outbreak. Methods: 362 Wenchuan earthquake survivors were assessed for Patient Heath Questionnaire, Generalized Anxiety Disorder Scale, as well as Multidimensional Scale of Perceived Social Support, as part of an online survey during between February 3 to February 10, 2020. Results: Our results showed that 6.6% and 4.7% of the participants experienced depression and anxiety during the COVID-19 outbreak, respectively. Perceived social support was negatively association with depressive and anxiety symptoms. Earthquake exposure has not a direct effect on current depressive and anxiety symptoms, while have moderates the relationship between perceived social support and psychological symptoms. Conclusions: Our findings suggested that trauma exposure may lead to salutogenic outcomes. The protective effect of perceived social support on psychological symptoms was greater in people with higher level of trauma exposure than in a lower one.